Technical Efficiency of Maternal and Reproductive Health Services in Public Hospitals of Oromia Regional State, Ethiopia - Kiddus Yitbarek; Ayinengida Adamu; Gebeyehu Tsega; Yibeltal Siraneh; Belay Erchafo; Delenasaw Yewhalaw; Firew Tekle; Mirkuzie Woldie (SAGE Publishing, 2019)
As the Ethiopian health system faced critical resource constraints, wise use of the available health resources is a priority agenda. Therefore, our study aimed to assess technical efficiency of maternal and reproductive health services in public hospitals of Oromia regional state, Ethiopia. Two-stage data envelopment analysis was performed among 14 hospitals with input orientation and variable returns to scale assumptions. Technical efficiency scores were computed at the first stage, and predictors were determined using Tobit regression at the second stage. The assessment revealed that 12 (85.7%) hospitals were pure technical efficient and 9 (64.29%) hospitals were scale efficient. Level (primary/general) (β = 1.17, 95% confidence interval [CI] = 0.16-2.18), service years (β = 0.02, 95% CI = 0.003-0.03), and size of catchment population (β = 5.58E-07, 95% CI = 2.95E-08 to 1.09E-06) were positively associated with technical efficiency of maternal and reproductive health service, whereas average waiting time for maternal health service (β = -0.03, 95% CI = -0.05 to −0.01) was negatively associated with efficiency. In conclusion, most of the hospitals were technically efficient and around two-thirds were operating scale efficient. Allocation of more resources to older secondary hospitals with larger catchment population could result in more efficient use of resources for maternal and reproductive health service delivery.